KOMPARASI FAKTOR DOMINAN MEMPENGARUHI PERILAKU PEMBELIAN TIKET WISATAWAN NUSANTARA KE BALI (SEBELUM PANDEMI – ERA PANDEMI) - Dewi, NGAS. (Jurnal IPTA (Industri Perjalanan Wisata); Vol 10 No 2 (2022): Jurnal IPTA (December 2022), 2023)
This article discusses the comparison of the dominant factors in the behaviour of nusantara tourists in purchasing plane tickets to the island of Bali Island, before and during the Covid-19 pandemic outbreak. The study is viewed from secondary data with data taken from two studies that have been conducted related to the behavioural factors of buying tickets for domestic tourists to Bali. The findings in this study explain that the dominant factor in the behaviour of domestic tourists buying airline tickets to Bali before the pandemic is psychological factors, namely (1) family factors, (2) self-desire factors, (3) security factors, (4) factors on timeliness, (5) the image of the airline, (6) the travel experience factor, (7) the knowledge factor of the airline, (8) the friendliness of airline services, (9) the availability of additional facilities, (10) the boarding service factor, and (11) baggage drop-off speed factor. Meanwhile, the dominant factors in the behaviour of domestic tourists buying tickets to Bali during the Covid-19 pandemic are (1) the influence factor from the closest people (other than family); (2) social strata factor; (3) the influence of the family; (4) the factor of family loyalty to this airline; (5) social status factor; (6) the family's trust factor in this airline; (7) social role factors; (8) the factor of feeling proud to have used this airline; (9) airline image factor. This study implies that the behaviour of domestic tourists tends to change due to the increase in prestige/social status gained by domestic tourists because not everyone can travel during the economic recession. It is hoped that airline companies will be able to optimize better service to prospective passengers who have social class (prestige) levels.